Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/8640999
|View full text |Cite|
|
Sign up to set email alerts
|

The Value of MRI Combined with AFP, AFP-L3, GP73, and DCP in the Diagnosis of Early Primary Liver Cancer

Abstract: Objective. To investigate the diagnostic value of magnetic resonance imaging (MRI) combined with serum alpha-fetoprotein (AFP), alpha-fetoprotein (AFP-L3), Golgi protein 73 (GP73), and des-γ-carboxyprothrombin (DCP) on early-stage primary liver cancer (PHC). Methods. A total of 122 patients who were treated in our hospital from January 2019 to May 2022 were included in this study, including 62 patients with early PHC (referred to as the observation group) and 60 patients with benign liver disease (referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Primary liver cancer (LC) is the sixth most common cancer and the third leading cause of cancer-related deaths worldwide [ 1 ]. Since most LC is insidious and progresses promptly, the onset of symptoms is generally at an advanced stage [ 2 , 3 ]. Alpha-fetoprotein (AFP) is a well-known and extensively used clinical diagnostic biomarker for primary LC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary liver cancer (LC) is the sixth most common cancer and the third leading cause of cancer-related deaths worldwide [ 1 ]. Since most LC is insidious and progresses promptly, the onset of symptoms is generally at an advanced stage [ 2 , 3 ]. Alpha-fetoprotein (AFP) is a well-known and extensively used clinical diagnostic biomarker for primary LC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%